Mononuclear phagocytes - origins, fates and functions - Jung, Steffen (Henry Stewart Talks, 2012)
Distinct development of macrophages and dendritic cells, Distinct functions of dendritic cells and macrophages in the maintenance of gut homeostasis, The role of inflammatory monocyte infiltrates in gut inflammation